Self-Concept and Prosocial Behavior Tendency for Accidents on Highways in UMSIDA Students - Danang Kurniawan; Nur Habibah (Psikologia : Jurnal Psikologi, 2015)
This study aimed to determine the relationship of self-concept and prosocial behavior tendency for accidents on the highway of the Sidoarjo Muhammadiyah University (Umsida) Students. The samples used sampling techniques incidental to the students at the Umsida who were still being active in the 2012-2013 with 254 students as research subjects. Based on the results of the analysis techniques of Pearson Product Moment correlation obtained rxy value of 0.743 with a significance value = 0.000, p <0.05. This means that the more positive self-concept, the higher the tendency of prosocial behavior on the highway accidents on the Umsida Students. Conversely the more negative self-concept, the lower the tendency of prosocial behavior on highway accidents on the Umsida Students.